THE EFFECT OF TEMPERATURE AND ROASTING TIME ON CHANGES IN THE CHARACTERISTICS AND PHYSICAL PROPERTIES OF SOLOK ARABIKA COFFEE BEANS - K, Arwizet.; Leni, Desmarita; Peng, Lim Hooi; Sumiati, Ruzita; Kusuma, Yuda Perdana (International Journal of Multidisciplinary Research and Literature, 2024)
High-temperature coffee roasting is a key initiator of the degradation of complex compounds in coffee beans, ultimately producing the desired taste and aroma for coffee enthusiasts. The aim of this research is to explore the influence of temperature and roasting duration on the changes in the mechanical properties of coffee beans using the conduction heat method. In this study, 500 grams of dried Arabica coffee with an initial moisture content of 12% were placed in a roasting apparatus equipped with a roasting machine. The heat source used was a gas stove, where the surface temperature of the roasting chamber was kept constant through a thermocouple temperature measuring device. The roasting process was carried out for 15 minutes at surface temperatures of 160°C, 180°C, 200°C, and 220°C, respectively. The final moisture content for each surface temperature was 3.72%, 3.65%, 2.13%, and 1.81%. Identification of the degree of roasting was conducted through the evaluation of the physical properties of coffee beans, including color, weight loss, moisture content, texture, and bean density. The decrease in hardness and density could be modeled using kinetic equations, while the color change was indicated by a decrease in the L, a, and b values. The research results confirm that roasting temperature significantly impacts the changes in the mechanical properties of coffee beans. The minimum temperature required to achieve satisfactory roasting levels is 180°C, while roasting at 200°C for 15 minutes produces coffee beans with optimal roasting levels. These findings provide new insights into optimizing the coffee roasting process to achieve the desired quality of coffee beans